Determinan Opini Audit Pemerintah Kabupaten/Kota di Sumatera Selatan - Muamar Wiralaksana; Rita Martini; Maria Maria (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Transparent and accountable regional financial management is a key focus in implementing good governance. A crucial instrument in providing financial management is the audit of financial statements by the Supreme Audit Agency (BPK), specifically the audit opinion, which is used as an indicator of the quality of regional government financial governance. The audit opinion reflects compliance with government accounting standards. However, some regions still experience fluctuations in audit opinions from year to year. The goal of the study is to determine how auditing works, how long it takes to complete an audit, how much land is available, and how much land is worth. This study covered 17 districts and cities in Sumatera Selatan between 2018 and 2022. Saturasi sampel is used for sampling, and the total number of samples is 155. Agency theory is used to explain the relationship between agents and directors. Logistic regression is used in data analysis. The analysis revealed that audit findings significantly negatively impacted the audit opinion. The greater the number of findings, the lower the quality of the financial statements and the potential for a lower audit opinion. However, the audit opinion was not determined by follow-up on audit findings, local revenue, or regional expenditure. Audit follow-up had no effect, but showed a positive trend, indicating that follow-up remains important even though it does not directly affect the audit opinion. Meanwhile, local revenue and regional expenditure had no significant effect and showed a negative trend, indicating that improvements in revenue and expenditure management do not guarantee an improvement in the audit opinion. The research's implications indicate that to increase public trust in financial management, local governments need to follow up on audit findings on local revenue and spending as a form of accountability to the public for any indications of state financial losses. The research also has a significant impact on explaining local governments' performance in managing their finances.